2022
DOI: 10.3389/fpsyg.2022.993122
|View full text |Cite
|
Sign up to set email alerts
|

Fertility decision of Iranian women during the COVID-19 pandemic and home quarantine: A cross-sectional study in Iran

Abstract: BackgroundFertility decision is defined as the mutual decision of partners toward having children, which may be equally controlled by the two partners or dominantly powered by the female partner. This study aimed to evaluate fertility decision of women during the COVID-19 pandemic in Iran.MethodsThis cross-sectional study was conducted on 600 women (300 pregnant and 300 non-pregnant) during the COVID-19 pandemic. A demographic questionnaire and the Attitudes toward Fertility and Childbearing Scale were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
2
10
0
Order By: Relevance
“…Nevertheless, our results are in line with previous studies covering more diverse populations 6,7,9,19,21 . Second, this is a cross-sectional study which examined changes in fertility desires due to the COVID-19 pandemic but did not test the actual fertility behaviour.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, our results are in line with previous studies covering more diverse populations 6,7,9,19,21 . Second, this is a cross-sectional study which examined changes in fertility desires due to the COVID-19 pandemic but did not test the actual fertility behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we also found that greater COVID exposure was associated with a decline in a desired number of children. In line with this, one study from Iran found that those women who were hospitalized during the pandemic had lower odds of having positive attitudes towards fertility 21 . One possible explanation for these findings is that women who were exposed to the SARS-CoV-2 infection might be more fearful about negative consequences of the virus on their and fetal health compared to those women who were not exposed to the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In their original research, 80 was established as a cut‐off score from a sample that contained a “community sample, primary care outpatients, general psychiatric outpatients, clinical trial of generalized anxiety disorder, and two clinical trials of PTSD” (Connor & Davidson, 2003 , p. 1). More recent work has established a mean score of 73% on the CD‐RISC‐25 for nurses working in intensive care units in New Zealand (Yu et al, 2019 ), 71% for nurses working in Iran responding to the COVID‐19 pandemic (Afshari et al, 2021 ), and 52% in an American sample of nurses working in LTC (Lin et al, 2021 ). Connor and Davidson ( 2003 ) have reported the Cronbach's alpha of the CD‐RISC‐25 scale to be 0.89, with a reliability coefficient of 0.87 reported for this scale through test–retest reliability in a four‐week interval (Connor & Davidson, 2003 ).…”
Section: Methodsmentioning
confidence: 99%